2017
DOI: 10.1007/s13770-017-0044-3
|View full text |Cite
|
Sign up to set email alerts
|

Surface Coating of Polytetrafluoroethylene with Extracellular Matrix and Anti-CD34 Antibodies Facilitates Endothelialization and Inhibits Platelet Adhesion Under Sheer Stress

Abstract: Expanded polytetrafluoroethylene (ePTFE) polymers do not support endothelialization because of nonconductive characteristics towards cellular attachment. Inner surface modification of the grafts can improve endothelialization and increase the long-term patency rate of the ePTFE vascular grafts. Here we reported a method of inner-surface modification of ePTFE vascular graft with extracellular matrix (ECM) and CD34 monoclonal antibodies (CD34 mAb) to stimulate the adhesion and proliferation of circulating endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 60 publications
(66 reference statements)
1
13
0
Order By: Relevance
“…After it had been shown that the cellular source of “fall out” healing was predominantly from endothelial precursor cells in the bone marrow ( 347 , 348 ) and that these endothelial progenitor cells (EPCs) express amongst other ligands the vascular endothelial growth factor receptor VEGFR-2, as well as the CD133 and CD34 antigens ( 349 351 ) several attempts were made to augment the homing of these cells onto “non-vital” synthetic grafts by immobilizing anti-ligand antibodies on the surface ( 352 , 353 ) including antibodies against chemotaxis stimulating receptors on stem cells ( 354 ). Yet, even with sporadic studies showing an enhanced recruitment of circulating cells ( 349 , 355 ), without a broad consensus to focus on endothelialisation and cell population from the circulation, this approach will continue to remain an unrealised promise. As such, transmural ingrowth and endothelialisation remain the most realistic modes of tissue regeneration for synthetic scaffolds.…”
Section: A Protracted Evolutionmentioning
confidence: 99%
“…After it had been shown that the cellular source of “fall out” healing was predominantly from endothelial precursor cells in the bone marrow ( 347 , 348 ) and that these endothelial progenitor cells (EPCs) express amongst other ligands the vascular endothelial growth factor receptor VEGFR-2, as well as the CD133 and CD34 antigens ( 349 351 ) several attempts were made to augment the homing of these cells onto “non-vital” synthetic grafts by immobilizing anti-ligand antibodies on the surface ( 352 , 353 ) including antibodies against chemotaxis stimulating receptors on stem cells ( 354 ). Yet, even with sporadic studies showing an enhanced recruitment of circulating cells ( 349 , 355 ), without a broad consensus to focus on endothelialisation and cell population from the circulation, this approach will continue to remain an unrealised promise. As such, transmural ingrowth and endothelialisation remain the most realistic modes of tissue regeneration for synthetic scaffolds.…”
Section: A Protracted Evolutionmentioning
confidence: 99%
“…Moreover, As shown in Table 1, all grafts exhibit a hemolysis rate much lower than 1%. The hemolysis rate of BC/CA-2 is 0.28%, which is lower than those of the ePTFE vascular graft (0.9%) reported by Chen et al 49 and an electrospun spider silk protein/PCL/ gelatin graft (0.3%) reported by Xiang et al 50 The formation of a complete endothelial layer on the surface of vascular grafts is crucially important to enhance long-term patency. 45,51 Endothelialization was monitored in vitro by seeding HUVECs onto BC, CA, and BC/CA grafts.…”
Section: In Vitro Characterizationmentioning
confidence: 67%
“…It is widely used in VTE for the development of grafts of a medium or large diameter, with a few of them being used for <6 mm scaffolds. The small diameter PTFE scaffolds show a high failure rate due to the formation of thrombi within them ( 95 ). These events occur because of the high hydrophobicity of PTFE, which favors platelet adhesion and activation of the coagulation cascade.…”
Section: Materials Used In Vtementioning
confidence: 99%
“…The presence of antibodies improved the hydrophilicity and decreased platelet adhesion on the scaffolds. In addition, the association of antibodies and ECM facilitated endothelization, adhesion and proliferation of endothelial cells ( 95 ). In another study, PTFE was associated with PEG.…”
Section: Materials Used In Vtementioning
confidence: 99%